Growth and hematological effects of cellulolytic Bacillus spp. isolated from rabbit gut - B. TURAEVA; G. J. KUTLIEVA; X. F. KAMOLOVA; M. A. NEMATOVA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Turaeva B, Kutlieva GJ, Kamolova XF, Nematofa MA. 2026. Growth and hematological effects of cellulolytic Bacillus spp. isolated from rabbit gut. Biodiversitas 27 (1): d270131. https://doi.org/10.13057/biodiv/d270131. This study aimed to isolate cellulolytic Bacillus strains from the rabbit gastrointestinal tract and evaluate their probiotic potential. Thirteen spore-forming isolates were obtained, of which Bacillus subtilis PBUZ-1 and PBUZ-3 exhibited the strongest cellulolytic activity. Both strains demonstrated high cellulase activity, with PBUZ-1 producing 1.69±0.16 U/mL in whey-based medium compared to 0.29±0.02 U/mL in Getchenson medium (p<0.001, Cohen’s d = 12.49). In vivo trials were conducted on Hikol rabbits supplemented with lyophilized strains (1 × 10⁶ CFU/g feed) for 30 days. Rabbits receiving probiotics showed superior growth performance, with body weights exceeding controls by 312-1050 g at 110-120 days (p<0.01, Cohen’s d = 2.45-3.83). Hematological analysis revealed significant increases in red and white blood cell counts, hemoglobin, and platelets (p<0.05). Biochemical profiles also improved, with higher total protein (65.17±2.24 g/L) and albumin (4.7±0.30 g/L), while bilirubin remained within physiological ranges. No adverse effects were observed, and physiological parameters such as temperature and heart rate stayed within normal limits. These findings demonstrate that rabbit gut-derived Bacillus subtilis strains enhance growth, hematological indices, and systemic health in rabbits. Importantly, this study provides the first evidence that such strains possess dual cellulolytic and probiotic functions, offering a safe and sustainable alternative to synthetic feed additives in rabbit farming and potentially other herbivorous livestock.